Hemolysin-producing Listeria monocytogenes affects the immune response to T-cell-dependent and T-cell-independent antigens. - Hage-Chahine, C M (1992)
A murine experimental infection with a hemolysin-producing (Hly+) strain of Listeria monocytogenes and a non-hemolysin-producing (Hly-) mutant was used as an in vivo model to evaluate the role of hemolysin production in the immune response. No antilisterial antibodies were detectable following sublethal infection with Hly+ bacteria, but consistent antilisterial immunoglobulin G (IgG) and IgM antibody production was observed following sublethal infection with the Hly- mutant. Hly+ but not Hly- L. monocytogenes induced transient inhibition of antibody response to Hly- bacteria and to unrelated T-cell-dependent (tetanus toxoid) and T-cell-independent (pneumococcal polysaccharide 3) antigens. Transient inhibition of the activation of an antigen-specific T-cell clone was also observed following Hly+ infection of antigen-presenting cells but not following Hly- infection. These results suggest that hemolysin production by L. monocytogenes is an important factor in modulating the immune response to T-cell-dependent and T-cell-independent antigens in infected individuals.